Irony in Mark Webb's 500 Days of Summer (2009) - Nugraha, Andita Shabirah Putri; Nurulaen, Yuyun; Sudarisman, Yoga (Journal of English Language and Education, 2025)
This research explores the use of irony in the film 500 Days of Summer (2009), directed by Mark Webb. Unlike typical romance films, this movie presents a non-linear narrative and avoids the usual happy ending, making it a rich subject for irony analysis. Using a qualitative descriptive method, the study identifies and explains different types of irony found in the film, including dramatic, situational, verbal, etc. These ironic moments are key to understanding the development of the main character, Tom Hansen, whose expectations about love often clash with reality. Scenes such as “Expectations vs. Reality” and the unexpected meeting with Autumn illustrate how irony shapes the story and reflects Tom’s emotional journey. The findings show that irony is a powerful narrative device that adds depth to the film, challenges traditional ideas about romance, and helps the audience connect more deeply with the character’s experience. This study highlights how irony can be used in film to reveal personal growth and present a more realistic view of love.